1971
DOI: 10.1017/s0022172400021653
|View full text |Cite
|
Sign up to set email alerts
|

Colonization resistance of the digestive tract in conventional and antibiotic-treated mice

Abstract: SUMMARYThe effect of oral administration of antibiotics on the intestinal flora of conventional mice and their resistance to colonization by orally introduced Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa was studied. Colonization resistance (CR) was expressed as the log of the oral bacterial dose followed by a persistent take in 50 % of the contaminated animals. The intestinal flora was virtually eliminated by the antibiotics and this elimination was accompanied by a precipitous fall of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
381
3
12

Year Published

1976
1976
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 778 publications
(405 citation statements)
references
References 11 publications
9
381
3
12
Order By: Relevance
“…The raw data were then transformed to eliminate most of their mutual dependence and to improve the linearity of remaining relations between the variables. Natural logarithms were computed, and combined into one size indicator (a) and three size-independent measures of shape (f1, f2 and c): a = log A, the natural logarithm of area, (1) fi= 2 logP-logA, the first form factor,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The raw data were then transformed to eliminate most of their mutual dependence and to improve the linearity of remaining relations between the variables. Natural logarithms were computed, and combined into one size indicator (a) and three size-independent measures of shape (f1, f2 and c): a = log A, the natural logarithm of area, (1) fi= 2 logP-logA, the first form factor,…”
Section: Methodsmentioning
confidence: 99%
“…Therefore it is clinically relevant to have fast monitoring methods for its ecological balance. This balance is sensitive to antibiotic treatment [1]. Various methods have been employed to study this influence: aerobic and anaerobic culturing [2][3][4][5][6][7][8], determination of the fatty acid pattern in faeces [3,9], and microflora associated characteristics [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The normal anaerobic flora of the oropharynx and GIT have a role in the prevention of colonization by GNAB, so called 'colonization resistance' [42,43]. The normal GIT flora also contribute to the maintenance of immunological homeostasis, and when abnormal can produce systemic depression of lymphocyte function [44].…”
Section: The Patientsmentioning
confidence: 99%
“…Antibiotic treatment of infection with oral, partially absorbed antibiotics or with antibiotics excreted with the bile, may therefore lead to a decrease in CR. A low 222 N. WIEGERSMA AND OTHERS CR permits yeasts and resistant bacteria to grow in the oropharynx and to high concentrations in the intestines; often to well over 108 bacteria/g faeces ( Van der Waaij et al 1971). This in turn may favour the transfer of R-factors between related species (Kasuya, 1964;Reed, Sieckmann & Georgi, 1969;Jones & Curtiss, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments (Van der Waaij et al 1971 have indicated that the mouse provides an ideal experimental model for the study of the influence of antibiotics on the CR; in the mouse a correlation has been shown between CR and the concentration of a resistant bacterium in the faeces, the relative weight of caecum (Koopman, Janssen & Druten, 1977), and the concentration of a dipeptide beta-aspartylglycine (Welling, 1979).…”
Section: Introductionmentioning
confidence: 99%